47 Systematic review and meta-analysis of analgesic efficacy and safety profile of single injection fascia iliaca compartment blocks in the acute pre-operative pain management of hip fractures. Issue 12 (23rd November 2017) - Fadhlillah, Fiqry; Chan, David
Abstract : Background: It is hypothesised that a single injection fascia iliaca compartment block (FICB) administered in the pre-operative setting provides better analgesic control for traumatic hip fractures and is not associated with major adverse effects. Systemic analgesics, whilst effective, could lead to cardiovascular, respiratory and cognitive impairment. As a consequence, undertreatment of acute pain remains prevalent in adult patients with hip fractures, with a consistent decline seen in analgesic administration with age. Objectives: Determine the analgesic efficacy and safety profile of single injection FICB performed in the pre-operative period for acute pain management in adult patients with traumatic hip fractures compared to other forms of analgesia. Methods: MEDLINE, EMBASE, Cochrane and CINAHL were independently searched to identify randomised controlled trials (RCTs) in English. Patients aged >18 years old who have suffered an isolated traumatic hip fracture (proximal femoral fracture) and received single injection FICB pre-operatively were included. No date restriction was applied and key journals and articles were scrutinised to include studies not identified by the primary search. Results: Out of 3757 citations, eight RCTs were included in the final quantitative analysis, comprising of 645 participants. Acute pain was significantly reduced in FICB during positioning and movement, standardised mean difference (SMD)=−1.82 (95% CI:−2.26 to −1.38, p<0.00001) but was variable at rest (p=0.20). There was a reduced incidence of analgesia breakthrough (n=57 versus n=73), drowsiness/sedation (n=1 versus n=22), desaturation (n=0 versus n=4) and nausea and vomiting (n=3 versus n=7) in the FICB arm. There were similar numbers of patients across both arms that reported localised bruising (n=3). Only one study was at low risk of bias. Conclusions: FICB is superior in controlling acute pre-operative pain in adult patients with traumatic hip fractures. The benefit is more evident during positioning and mobilisation of the limb. FICB has a better safety profile and reduces dependency on systemic analgesia.